Pomalidomide, bortezomib, and dexamethasone at first relapse in lenalidomide‐pretreated myeloma: A subanalysis of OPTIMISMM by clinical characteristics. (22nd September 2021) - Richardson, Paul G.; Schjesvold, Fredrik; Weisel, Katja; Moreau, Philippe; Anderson, Larry D.; White, Darrell; Rodriguez‐Otero, Paula; Sonneveld, Pieter; Engelhardt, Monika; Jenner, Matthew; Corso, Alessandro; Dürig, Jan; et al.
Abstract: Objective: We evaluated the efficacy and safety of pomalidomide, bortezomib, and dexamethasone (PVd) vs bortezomib and dexamethasone (Vd) by age, renal function, and high‐risk cytogenetic abnormalities in lenalidomide‐pretreated patients with multiple myeloma at first relapse. Methods: OPTIMISMM was a phase 3, multicenter, open‐label, randomized study (NCT01734928; N = 559). The primary endpoint was progression‐free survival (PFS). Results: Overall, 226 patients had received one prior line of therapy. PVd significantly prolonged PFS vs Vd in patients aged ≤65 years (median, 22.0 vs 13.1 months; P  = .0258) and >65 years (median, 17.6 vs 9.9 months; P  = .0369). Median PFS in patients with renal impairment (RI; creatinine clearance <60 mL/min) was 15.1 months with PVd vs 9.5 months with Vd (hazard ratio [HR], 0.67 [95% CI, 0.34‐1.34]). In patients without RI, median PFS was 22.0 vs 13.1 months (HR, 0.45 [95% CI, 0.27‐0.76]). In patients with high‐risk cytogenetics, median PFS was 14.7 vs 9.9 months (HR, 0.39 [95% CI, 0.13‐1.17]). PVd significantly improved overall response rate vs Vd in all subgroups. The safety profile of PVd was consistent with previous reports. Conclusions: These findings confirmed the benefits of PVd at first relapse, including in patients with poor prognostic factors.